The Role of Non-Farm Employment and Service Industries in Enhancing Rural Welfare - Shukrullo Muratov; Ekaterina Burova; Svetlana Suloeva; Shavkat Hasanov; Khusniddin Pardaev; Bokhodir Isroilov (International Journal of Technology)
This study aimed to explore how incomes from farm and nonfarm activities, the availability of social infrastructure, and proximity to essential service influence family welfare in rural areas. Data were obtained through a sociological survey of 1428 respondents who were heads of households in the Samarkand region villages. Social and economic well-being indices were created using the Factor Analysis model, and the relationship between family heads working in farm or nonfarm industries as well as income sources was examined. Additionally, the Latent Class (Gaussian) analysis model was used to classify households based on proximity to social infrastructure service, categorized as "close," "medium," and "long" distance. The service include food sales, shoe repair, tailoring, restaurants, hair salons, and catering. The results showed that the social and economic welfare of family decreased with each unit increase in the distance from rural homes to social infrastructure service. The relationship was statistically significant at 1% (***, p